Evaluasi Pembelajaran dalam Meningkatkan Kinerja Guru Di SMP Negeri Satap Raburia - Korosando, Fransiskus; Raji, Manggu Ngguna (LPPM Institut Pendidikan Nusantara Global, 2025)
This research is included in field research using a qualitative approach. In data collection, researchers use interview, observation, and documentation methods as data collection techniques. And the techniques chosen in data analysis are data reduction, data display and conclusion drawing. the results of the study can be concluded as follows: Planning for learning evaluation in improving teacher performance at SMP Negeri Satap Raburia, namely the Principal carries out planning by forming a performance evaluation committee team, in implementing this learning evaluation has applied existing principles. Although previously it has gone through the planning process, there are still obstacles in its implementation, to overcome them, cooperation and communication from all parties are needed.